Evaluation of Community Empowerment Initiatives in Dengue Hemorrhagic Fever Control and Prevention in Pekanbaru City: English - Lubis, Arga Abdi Rafiud Darajat; Agung, Vaqqi Riehanda; Lubis, Satia Negara (CV. ARGA FARMA, 2024)
This study aimed to evaluate the use of community empowerment strategies in dengue fever prevention and control in Pekanbaru City, with a focus on program inputs, outputs, and processes in relation to regional planning. Utilizing qualitative methods, the study relied heavily on informants to shape its findings. The